A Phase I, First‐in‐Human Study of GSK2849330, an Anti‐HER3 Monoclonal Antibody, in HER3‐Expressing Solid Tumors. (21st July 2021) - Gan, Hui K.; Millward, Michael; Jalving, Mathilde; Garrido‐Laguna, Ignacio; Lickliter, Jason D.; Schellens, Jan H.M.; Lolkema, Martijn P.; Van Herpen, Carla L.M.; Hug, Bruce; Tang, Lihua; O'Connor‐Semmes, Robin; Gagnon, Robert; et al.
Abstract: Background: GSK2849330, an anti‐HER3 monoclonal antibody that blocks HER3/Neuregulin 1 (NRG1) signaling in cancer cells, is engineered for enhanced antibody‐dependent cellular cytotoxicity and complement‐dependent cytotoxicity. This phase I, first‐in‐human, open‐label study assessed the safety, pharmacokinetics (PK), pharmacodynamics, and preliminary activity of GSK2849330 in patients with HER3‐expressing advanced solid tumors. Patients and Methods: Patients with various tumor types were prospectively selected for HER3 expression by immunohistochemistry; a subset was also screened for NRG1 mRNA expression. In the dose‐escalation phase, patients received GSK2849330 1.4–30 mg/kg every 2 weeks, or 3 mg/kg or 30 mg/kg weekly, intravenously (IV). In the dose‐expansion phase, patients received 30 mg/kg GSK2849330 IV weekly. Results: Twenty‐nine patients with HER3‐expressing cancers, of whom two expressed NRG1, received GSK2849330 (dose escalation: n  = 18, dose expansion: n  = 11). GSK2849330 was well tolerated. No dose‐limiting toxicities were observed. The highest dose, of 30 mg/kg weekly, expected to provide full target engagement, was selected for dose expansion. Treatment‐emergent adverse events (AEs) were mostly grade 1 or 2. The most common AEs were diarrhea (66%), fatigue (62%), and decreased appetite (31%). Dose‐proportional plasma exposures were achieved, with evidence of HER3 inhibition in paired tissue biopsies. Of 29 patients, only 1 confirmed partial response, lasting 19 months, was noted in a patient with CD74‐NRG1 ‐rearranged non‐small cell lung cancer (NSCLC). Conclusion: GSK2849330 demonstrated a favorable safety profile, dose‐proportional PK, and evidence of target engagement, but limited antitumor activity in HER3‐expressing cancers. The exceptional response seen in a patient with CD74‐NRG1 ‐rearranged NSCLC suggests further exploration in NRG1 ‐fusion–positive cancers. Implications for Practice: This first‐in‐human study confirms that GSK2849330 is well tolerated. Importantly, across a variety of HER3‐expressing advanced tumors, prospective selection by HER3/NRG1 expression alone was insufficient to identify patients who could benefit from treatment with this antibody‐dependent cell‐mediated cytotoxicity– and complement‐dependent cytotoxicity–enhanced anti‐HER3 antibody. The only confirmed durable response achieved was in a patient with CD74‐NRG1 ‐rearranged lung cancer. This highlights the potential utility of screening for NRG1 fusions prospectively across tumor types to enrich potential responders to anti‐HER3 agents in ongoing trials. Abstract : This phase I, first‐in‐human study assessed the safety, pharmacokinetics, pharmacodynamics, and preliminary activity of GSK2849330 in patients with HER3‐expressing advanced solid tumors.